Filtration rates in inorganic filters submitted to different repose periods - doi: 10.4025/actascitechnol.v35i2.14391 (Acta Scientiarum. Technology, 2012)
This work aimed to evaluate the filtration rate in organic filters after being subjected to different repose periods in the primary treatment of swine wastewater (SWW). Filtration columns were mounted in PVC pipes measuring 100 mm in diameter and 600 mm in length and filled with 2-5 mm sawdust particles. Five different repose periods were evaluated: 1, 2, 4, 8 and 16 days after the first filtration, carrying out three batches. The SWW filtration rate decreased with the operating time of the filters, which can be attributed to clogging of pores resulting from high concentrations of suspended solids (SS) present in this type of wastewater. In the three batches, it was observed that the repose periods of 1, 2 and 4 days were not sufficient to unclog the pores, however, repose periods of 8 and 16 days for the filter medium resulted in increases of the filtration rate, only 59 and 72% of the initial rate, respectively. Â